Neuropeptide Y-expressing dorsal horn inhibitory interneurons gate spinal pain and itch signalling - Kieran A Boyle; Erika Polgar; Maria Gutierrez-Mecinas; Allen C Dickie; Andrew H Cooper; Andrew M Bell; Evelline Jumolea; Adrian Casas-Benito; Masahiko Watanabe; David I Hughes; Gregory A Weir; John S Riddell; et al. (eLife, 2023)
Somatosensory information is processed by a complex network of interneurons in the spinal dorsal horn. It has been reported that inhibitory interneurons that express neuropeptide Y (NPY), either permanently or during development, suppress mechanical itch, with no effect on pain. Here, we investigate the role of interneurons that continue to express NPY (NPY-INs) in the adult mouse spinal cord. We find that chemogenetic activation of NPY-INs reduces behaviours associated with acute pain and pruritogen-evoked itch, whereas silencing them causes exaggerated itch responses that depend on cells expressing the gastrin-releasing peptide receptor. As predicted by our previous studies, silencing of another population of inhibitory interneurons (those expressing dynorphin) also increases itch, but to a lesser extent. Importantly, NPY-IN activation also reduces behavioural signs of inflammatory and neuropathic pain. These results demonstrate that NPY-INs gate pain and itch transmission at the spinal level, and therefore represent a potential treatment target for pathological pain and itch.